2009
DOI: 10.1111/j.1539-6924.2009.01253.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Four Exposure Pathways to Influenza Infection Risk

Abstract: The relative contribution of four influenza virus exposure pathways-(1) virus-contaminated hand contact with facial membranes, (2) inhalation of respirable cough particles, (3) inhalation of inspirable cough particles, and (4) spray of cough droplets onto facial membranes-must be quantified to determine the potential efficacy of nonpharmaceutical interventions of transmission. We used a mathematical model to estimate the relative contributions of the four pathways to infection risk in the context of a person a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
220
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(226 citation statements)
references
References 31 publications
(52 reference statements)
5
220
0
1
Order By: Relevance
“…Alford et al 25 showed that three times the TCID50 was needed to infect volunteers via bioaerosols; this compares to other studies showing that 127-320 TCID50 are needed to initiate infection by the intranasal route. 44 Using these data, attempts have been made to estimate the risk of infection attributable to the different routes of infection, 45 but the outputs of such models are only ever as good as the input assumptions. However, if Alford et al 's 25 supposition is true then even small quantities of viable virus expressed via bioaerosols might have significant infectious potential.…”
Section: Discussionmentioning
confidence: 99%
“…Alford et al 25 showed that three times the TCID50 was needed to infect volunteers via bioaerosols; this compares to other studies showing that 127-320 TCID50 are needed to initiate infection by the intranasal route. 44 Using these data, attempts have been made to estimate the risk of infection attributable to the different routes of infection, 45 but the outputs of such models are only ever as good as the input assumptions. However, if Alford et al 's 25 supposition is true then even small quantities of viable virus expressed via bioaerosols might have significant infectious potential.…”
Section: Discussionmentioning
confidence: 99%
“…(25) The limited number of models results, in part, from the difficulty in obtaining the detailed activity data needed to generate quantified estimates of contact rates between hands and fomites, hands and mucus membranes, and fomites and mucus membranes. Measurements of contact rates are difficult because of the high frequency and relatively short duration of these activities.…”
Section: Introductionmentioning
confidence: 99%
“…(1) However, the relative importance of these routes of transmission is unclear and appears to depend on multiple factors, including temperature and humidity, the virus concentration in respiratory secretions, the distance from the source to the recipient, and the genotype of the virus. (2,3) The possibility of airborne transmission in particular is hotly debated, with some studies suggesting that this pathway plays a critical role in the spread of influenza (1,4) while others concluding that it does not. (5) This controversy had a direct impact on public health policy during the 2009 novel H1N1 influenza pandemic; some health care institutes such as the U.S. Institute of Medicine recommended that health care workers in close contact with influenza patients wear respirators to prevent possible airborne transmission, (6) while other organizations such as the World Health Organization did not.…”
Section: Introductionmentioning
confidence: 99%